Sodium alginate/β-cyclodextrin as supramolecular hydrogel for adsorption of perfluorooctane sulfonate - Kamaruzaman, Sazlinda; Abdul Rahman, Norizah; Yahaya, Noor Fatimah; Loh, Saw Hong; Md Shukri, Dyia Syaleyana; Zakaria, Aiza Farhani (Universiti Kebangsaan Malaysia, 2024)
Perfluorooctane sulfonate (PFOS) has been classified as a persistent organic pollutant that contributes to water pollution due to its slow environmental degradation properties. Due to the need for effective removal of PFOS from polluted water bodies, a supramolecular hydrogel incorporating sodium alginate and β-cyclodextrin (SA-β-CD hydrogel) was developed to facilitate the entrapment of PFOS. The adsorption study has been utilised to remove PFOS via batch experiment procedure on several adsorptive parameters such as pH, contact time and initial concentration. The optimum conditions with a dose of 1280 mg of SA-β-CD hydrogels beads were applied at 70°C, contact time of 30 minutes, pH of 5.5, 10 mL of 10.0 ppm of PFOS solution, and 250 rpm of stirring rate were reported. The adsorption capacity and efficiency removal of PFOS by SA-β-CD hydrogel beads has achieved up to 0.0764 mg/g and 84.72%, respectively. Based on the data obtained, the adsorption kinetic study, which follows a pseudosecond-order model, was fitted to illustrate the adsorption of PFOS by SA-β-CD hydrogel beads, with an R² value of 0.990. The adsorption isotherm study showed that the adsorption of PFOS by SA-β-CD hydrogel beads fits the Langmuir isotherm model, with an R² value of 0.987. The adsorption of PFOS occurs as a monolayer/single layer and involves chemisorption to the hydrogel beads. Therefore, this work demonstrates that SA-β-CD hydrogel beads may be useful in controlling environmental water pollution